Cardiac ECMO for biventricular hearts after paediatric open heart surgery. Issue 5 (14th April 2004) - Chaturvedi, R R; Macrae, D; Brown, K L; Schindler, M; Smith, E C; Davis, K B; Cohen, G; Tsang, V; Elliott, M; de Leval, M; Gallivan, S; Goldman, A P
Abstract : Objective: To delineate predictors of hospital survival in a large series of children with biventricular physiology supported with extracorporeal membrane oxygenation (ECMO) after open heart surgery. Results: 81 children were placed on ECMO after open heart surgery. 58% (47 of 81) were transferred directly from cardiopulmonary bypass to ECMO. Hospital survival was 49% (40 of 81) but there were seven late deaths among these survivors (18%). Factors that improved the odds of survival were initiation of ECMO in theatre (64% survival (30 of 47)) rather than the cardiac intensive care unit (29% survival (10 of 34)) and initiation of ECMO for reactive pulmonary hypertension. Important adverse factors for hospital survival were serious mechanical ECMO circuit problems, renal support, residual lesions, and duration of ECMO. Conclusions: Hospital survival of children with biventricular physiology who require cardiac ECMO is similar to that found in series that include univentricular hearts, suggesting that successful cardiac ECMO is critically dependent on the identification of hearts with reversible ventricular dysfunction. In our experience of postoperative cardiac ECMO, the higher survival of patients cannulated in the operating room than in the cardiac intensive care unit is due to early effective support preventing prolonged hypoperfusion and the avoidance of a catastrophic cardiac arrest.